Sosialisasi Data Bicara, Statistik Menjawab: Dari Hipotesis ke Kesimpulan (Perspektif Metode Penelitian) - Primadi Candra Susanto; Lily Yuntina (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program was carried out to strengthen the ability of lecturers, students, and practitioners in understanding the role of data and statistics as the foundation for constructing scientific arguments in quantitative research. The activity originated from the limited understanding of some participants regarding the correct logical flow of research, starting from problem formulation, hypothesis development, data processing, to drawing conclusions based on analytical results. Through case-based training and interactive discussions, participants were introduced to key concepts in research methodology, such as determining variables, sampling techniques, developing measurement instruments, and applying parametric and non-parametric statistics to test hypotheses. The training emphasized that data provide factual descriptions of a phenomenon, while statistics serve as analytical tools that answer research questions objectively. The activity was conducted online with 73 participants from Universitas Pancasakti Bekasi, representing various academic backgrounds. The results indicated an improvement in participants' ability to understand statistical outputs, interpret significance levels of tests, and prepare research conclusions in a logical and structured manner. In addition, the activity contributed to enhancing methodological literacy within the academic community, encouraging a strong research culture, and maximizing the use of statistics in scientific analysis as well as professional practice. Therefore, this program has a positive impact on improving the quality of research in higher education.